Maternal Characteristics and Child Malnutrition in Indonesia, 2014/2015 (Journal of Economic Education, 2022)
Child malnutrition is a condition of disproportionate nutrition in children. It manifests in three forms—stunting, being underweight, and wasting. It is one of the biggest burdens in Indonesia, as the incidence shows an improvement, but it continues to be categorized as highly severe for stunting and being underweight and moderately severe for wasting. Using the Indonesian Family Life Survey (IFLS) Wave 5 data year 2014/2015, this study analyzes the association between maternal characteristics and the incidence of malnutrition among children aged 5–59 months in Indonesia. The probit regression result implies that maternal characteristics (mother’s BMI, height, and education) significantly influence the child’s malnutrition. Furthermore, there are other compounding factors to consider, such as the child’s age, the number of members in a household, the household’s per capita expenditure, and the household’s area and region.